Update on human papillomavirus - Part II: complementary diagnosis, treatment and prophylaxis, - Marcelo Grossi Araújo; Geraldo Magela Magalhães; Lucas Campos Garcia; Érica Cristina Vieira; Maria de Lourdes Ribeiro de Carvalho-Leite; Antônio Carlos Martins Guedes (Sociedade Brasileira de Dermatologia, 2021)
Abstract In this nonsystematic review, the complementary diagnosis, treatment, prevention, and control of human papillomavirus are discussed. The histopathology is addressed regarding its indications, main findings and limitations, as a complementary diagnostic method largely used by dermatologists. Electron microscopy is briefly reviewed, along with its contribution to the accumulated knowledge on HPV, as well as the relevance of research in using this technology for future advances in diagnosis and treatment. Molecular information about the virus is continuously increasing, and the practical applications of HPV serology, molecular identification and genotyping are discussed. Vaccines are a valuable tool in primary HPV infection prevention and are now available in many countries; their composition, indications, and adverse effects are revisited. Local and systemic treatment options are reviewed and off-label prescriptions are discussed. Finally, health education focusing on HPV infection as a sexually transmitted infection of worldwide relevance and the many barriers to improve primary and secondary prevention are addressed.